A flexible piezoresistive sensor based on conductive nanofibers and its preparation method and application

Through the preparation method of flexible piezoresistive sensors of conductive nanofibers, the problems of narrow working range and insufficient sensitivity of traditional sensors are solved, and the effects of high sensitivity and wide working range are achieved, which are suitable for a variety of application fields.

CN117433672BActive Publication Date: 2024-12-17SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311213329.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2024-12-17
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

The application of traditional flexible piezoresistive sensors in wearable devices and human-computer interaction is limited by the problem of their narrow working range and insufficient sensitivity.

Method used

The flexible piezoresistive sensor preparation method of conductive nanofibers is prepared by electrospinning method, and the conductive fiber membrane and flexible fiber electrode are combined and packaged through layer-layer stacking to improve the binding force between conductive particles and fibers, and improve the sensitivity of the sensor and Work scope.

Benefits of technology

It realizes flexible piezoresistive sensors with high sensitivity and wide working range, suitable for wearable devices, human-computer interaction and smart medical fields, and has the advantages of stability, low cost and rapid response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117433672B_ABST
    Figure CN117433672B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of polymer fibers, and specifically relates to a flexible piezoresistive sensor based on conductive nanofibers, and a preparation method and application thereof. The method comprises the following steps: using an electrospinning method to prepare a flexible polymer mixed fiber membrane from polymer compounds, polyacrylonitrile and Pluronic F127, and then placing it in an oxidant solution to react to obtain a conductive fiber membrane; after preparing a flexible nanofiber substrate by electrospinning, applying silver paste and drying to obtain a flexible fiber electrode; compounding the flexible fiber electrode and the conductive fiber membrane by stacking them layer by layer, and finally encapsulating them into a sensor by a sticky flexible film by clipping and pasting. The sensor has the advantages of a wide detection range, high sensitivity, good stability, short response time, etc., and has broad market development and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer fibers, and in particular relates to a flexible piezoresistive sensor based on conductive nanofibers, and a preparation method and application thereof. Background Art

[0002] In recent years, mechanical sensors, as the most important component of smart electronic products, have attracted widespread attention. Mechanical sensors can convert physical stimuli into measurable electrical signals. According to their working mechanism, they can be divided into four types: piezoresistive, piezocerometric, piezoelectric and triboelectric. Compared with mechanical sensors such as capacitive sensors, piezoelectric sensors, and friction sensors, flexible piezoresistive sensors have attracted much attention due to their advantages such as simple signal reading, easy preparation, high sensitivity, and wide detection range. They are widely used in the detection of human motion and diseases. However, traditional flexible piezoresistive mechanical sensors focus on the pursuit of high sensitivity, but ignore the problem that the working range of flexible piezoresistive sensors is too narrow, which greatly limits their further application in wearable devices, human-computer interaction, and electronic skin. In order to solve the above problems, Chinese patent application CN202010875844.6 proposes to use a polyurethane sponge fracture structure to improve the corresponding sensitivity and working range, but its working range is still relatively low. Summary of the invention

[0003] In order to address the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a flexible piezoresistive sensor based on conductive nanofibers, thereby improving the binding force between conductive particles and fibers, thereby further improving the working range and sensitivity of the entire flexible piezoresistive sensor.

[0004] Another object of the present invention is to provide a flexible piezoresistive sensor based on conductive nanofibers. The flexible piezoresistive sensor has simple materials, is easy to prepare, can be used for a long time, is easy to operate, has reasonable cost, and can be prepared on a large scale.

[0005] Another object of the present invention is to provide an application of the above-mentioned flexible piezoresistive sensor based on conductive nanofibers.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a flexible piezoresistive sensor based on conductive nanofibers comprises the following steps:

[0008] S1. Preparation of conductive fiber membrane: polymer compound, polyacrylonitrile (PAN) and polyoxyethylene-polyoxypropylene-polyoxyethylene (Pluronic F127) are dissolved in an organic solvent to obtain a spinning solution, and then electrospinning is performed to obtain a flexible polymer mixed fiber membrane;

[0009] The prepared flexible polymer hybrid fiber membrane is placed in an oxidant solution, left to stand for a period of time, and then a conductive monomer solution is added to react for 4 to 20 hours, and a conductive fiber membrane is obtained after the reaction is completed; the mass ratio of the conductive monomer to the oxidant is 1:1 to 8:1;

[0010] S2. Preparation of flexible fiber electrodes: a polymer compound is dissolved in an organic solvent to obtain a spinning solution and electrospinning is performed to obtain a flexible nanofiber substrate; then, a silver paste is brushed on the middle of the obtained flexible nanofiber substrate and dried to obtain a flexible fiber electrode;

[0011] S3. The prepared flexible fiber electrode and the conductive fiber membrane are compounded together by stacking them layer by layer, and finally a sticky flexible film is used to package them into a sensor by sandwiching and pasting.

[0012] The polymer compound described in step S1 includes: at least one of polyvinyl alcohol (PVA), polystyrene (PS), polyvinylidene fluoride (PVDF), polyamide, polyacrylic acid (PAA) and polycaprolactone (PCL), the mass ratio of the polymer compound, polyacrylonitrile (PAN) and polyoxyethylene-polyoxypropylene-polyoxyethylene (Pluronic F127) is 5:4:1-8:1:1, and the sum of the mass of the polymer compound, polyacrylonitrile and Pluronic F127 accounts for 8wt%-20wt% of the mass of the spinning solution.

[0013] In step S1, if two polymers are added to the polymer compound, the mass ratio of any two polymers added is 3:7 to 7:3; if three polymers are added, the mass ratio of any three polymers added is 3:6:1 to 7:2:1.

[0014] In step S1, the order of adding materials when preparing the spinning solution is: first add the polymer compound, then add polyacrylonitrile, and then add an organic solvent to dissolve it, and then add Pluronic F127 after it is evenly dissolved; the polymer compound, polyacrylonitrile (PAN) and polyoxyethylene-polyoxypropylene-polyoxyethylene are all added with an organic solvent and stirred at 50-100° C. for 6-12 hours to obtain the spinning solution;

[0015] The organic solvent described in step S1 is at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), acetone, tetrahydrofuran (THF), deionized water, and toluene.

[0016] First add the polymer compound and polyacrylonitrile, then add the organic solvent to dissolve evenly, and then add Pluronic F127. This order of adding materials can make Pluronic F127 dispersed more evenly in the entire solution, which is conducive to the uniform distribution of the conductive particles on the fiber.

[0017] The electrospinning parameters described in step S1 are: spinning voltage 9-25 kV, receiving distance 7-40 cm, drum speed 100-5000 rpm, spinning solution supply rate 0.5 ml / h-4 ml / h, spinning time 4-10 h, spinning environment temperature 5-60 ° C, relative humidity 20-80 RH%.

[0018] The oxidant in step S1 is preferably at least one of FeCl3·6H2O, ammonium persulfate, and sulfuric acid, and the conductive monomer is preferably pyrrole (Py) or aniline; the concentration of the oxidant solution is 1g / L~10g / L, preferably 1g / L~5g / L; the mass ratio of the oxidant to the conductive monomer is preferably 1:1~5:1; the flexible polymer hybrid fiber membrane is placed in the oxidant solution and allowed to stand at -10℃~10℃ for 0.5h~3h.

[0019] In step S1, after the conductive fiber membrane is prepared, it is further washed with deionized water for multiple times and then dried at 60° C. for 1 hour.

[0020] The polymer compounds described in step S2 are all elastic polymer compounds, specifically: one of polyurethane (TPU), polyethylene terephthalate (PET), polystyrene-polybutadiene-polystyrene (SBS) and polyamide; the organic solvent described in step S2 is at least one of N,N-dimethylformamide (DMF), tetrahydrofuran (THF), acetone, formic acid, toluene, and chloroform.

[0021] The spinning solution in step S2 is prepared by dissolving the polymer compound in an organic solvent and stirring the mixture at 60 to 100° C. for 6 to 18 hours to obtain the spinning solution.

[0022] The electrospinning parameters in step S2 are: spinning voltage of 9 to 40 kV, receiving distance of 9 to 40 cm, drum speed of 100 to 5000 rpm, spinning solution supply rate of 0.5 ml / h to 1.5 ml / h, spinning time of 4 to 15 h, spinning environment temperature of 5 to 40 ° C, and relative humidity of 20 to 90 RH%.

[0023] In step S2, the flexible nanofiber substrate is cut into a suitable shape and then coated with silver paste. The silver paste with an area of ​​half that of the flexible nanofiber substrate and a thickness of 50 μm to 200 μm is evenly coated in the middle of the cut flexible nanofiber substrate. The size of the cut flexible nanofiber substrate in step S2 should be larger than that of the conductive fiber film. The flexible nanofiber substrate coated with silver paste is dried in an infrared lamp or oven for 10 to 40 minutes and then placed in the middle of a sticky flexible film.

[0024] When assembling the sensor in step S3, the conductive nanofiber film is stacked in 1 to 5 layers, aligned layer by layer, and placed between upper and lower flexible electrodes placed orthogonally;

[0025] The adhesive flexible film in step S3 can be made of one of the following materials: Kapton tape, 3M tape, polyethylene (PE) film, polydimethylsiloxane (PDMS) film, etc.

[0026] The sensor assembled in step S3 has a wide working range and high sensitivity and can be applied to fields such as wearable devices, human-computer interaction, electronic skin and smart medical care.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] 1. The method for binding conductive nanoparticles to fiber membranes provided by the present invention has readily available raw materials and is simple to operate. The interfacial bonding force between the conductive particles and the fiber membranes is effectively improved, and the introduction of the fiber structure also greatly improves the sensitivity, allowing for large-scale stable preparation.

[0029] 2. The conductive nanofibers prepared by the present invention have the advantages of high porosity and aspect ratio. Since polypyrrole has excellent electron transport ability, a flexible piezoresistive sensor with excellent sensitivity is prepared.

[0030] 3. The technical solution of the present invention has the advantages of simple preparation process, low cost, and mass production. At the same time, the prepared flexible piezoresistive sensor has good stability (>10,000 times) and high sensitivity (~996 kPa -1 ) and a fast response speed (~12ms) and a wide detection range (<1MPa). It has broad application prospects in wearable devices, flexible electronic skin and human-computer interaction in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of the conductive fiber prepared in Example 1. In the image, it can be clearly seen that the polypyrrole particles are bonded to the fiber.

[0032] Figure 2 This is a scanning electron microscope image of the conductive fiber prepared in Example 2. In the image, it can be clearly seen that the polypyrrole particles are bonded to the fiber.

[0033] Figure 3 This is a scanning electron microscope image of the conductive fiber prepared in Example 3. In the image, it can be clearly seen that the polypyrrole particles are bonded to the fiber.

[0034] Figure 4 This is a scanning electron microscope image of the conductive fiber prepared in Example 4. In the image, it can be clearly seen that the polypyrrole particles are bonded to the fiber.

[0035] Figure 5 This is a transmission electron microscope image of the conductive fiber prepared in Example 3. In the image, it can be clearly seen that the polypyrrole particles are bonded to the fiber.

[0036] Figure 6 This is a physical picture of the flexible piezoresistive sensor prepared in Example 7.

[0037] Figure 7 This is a response curve diagram of the flexible piezoresistive sensor prepared in Example 4 at different frequencies (IT curve changes at different operating speeds of the single-axis motion controller). It can be seen that the prepared sensor responds to pressure velocities at different frequencies and is easy to distinguish from each other.

[0038] Figure 8 This is a response curve diagram of the flexible piezoresistive sensor prepared in Example 3 under different pressures. In the figure, the IV curve shows the internal ohmic contact of the sensor under different static pressures. As the resistance continues to decrease, the slope of the IV curve increases with the increase of pressure.

[0039] Fig. 9 This is a curve diagram of the flexible piezoresistive sensor prepared in Example 6 after more than 15,000 fatigue cycles at 5 kPa. After 15,000 continuous loading-unloading cycles at 5 kPa, the repeatability is good. Figure a in the figure is the IT curve of the first 6 cycles, and Figure b is the IT curve of the last 6 cycles. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.

[0041] The silver paste described in the embodiment is a commercially available conductive silver paste with a solid content of 65%; the pyrrole (Py) solution is a commercially available product with a solution mass concentration of 99%.

[0042] Example 1

[0043] Preparation of conductive fiber membrane: Polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 6:3:1 at 60°C, wherein the sum of the mass of PVDF, PAN, and Pluronic F127 accounted for 10wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 8 hours. The spinning solution was then electrospun at a voltage of 10.5kV, a receiving distance of 13cm, a drum speed of 100rpm, a solution supply rate of 0.6ml / h, a temperature of 32°C, and a humidity of 48RH%, to obtain a flexible PVDF / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0044] 0.4 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 6 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0045] Preparation of flexible fiber electrodes: The polymer TPU is completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 1:1 at 80°C, stirred for 12 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution is subjected to electrostatic spinning, with a spinning voltage of 14kV, a receiving distance of 20cm, a drum speed of 100rpm, a solution supply rate of 0.5ml / h, a temperature of 30°C, and a humidity of 50RH%, to obtain TPU nanofibers. The obtained nanofibers are cut into 20mm×20mm squares, and a silver paste with an area of ​​10mm×20mm and a thickness of 100μm is brushed in the middle of the square, and then placed under an infrared baking lamp for drying to obtain a flexible fiber electrode;

[0046] The prepared conductive fiber membranes were neatly stacked in three layers and placed between orthogonally placed upper and lower flexible fiber electrodes, and finally packaged into a sensor using PI tape.

[0047] Example 2

[0048] Preparation of conductive fiber membrane: Polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 6:3:1 at 60°C, wherein the sum of the mass of PVDF, PAN, and Pluronic F127 accounted for 12wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 8 hours. The spinning solution was then electrospun at a voltage of 10.5kV, a receiving distance of 13cm, a drum speed of 100rpm, a solution supply rate of 0.6ml / h, a temperature of 32°C, and a humidity of 48RH%, to obtain a flexible PVDF / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0049] 0.4 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 6 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0050] Preparation of flexible fiber electrodes: The polymer TPU is completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 1:1 at 80°C, stirred for 12 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution is subjected to electrostatic spinning, with a spinning voltage of 14kV, a receiving distance of 20cm, a drum speed of 100rpm, a solution supply rate of 0.5ml / h, a temperature of 30°C, and a humidity of 50RH%, to obtain TPU nanofibers. The obtained nanofibers are cut into 20mm×20mm squares, and a silver paste with an area of ​​10mm×20mm and a thickness of 100μm is brushed in the middle of the square and then dried to obtain a flexible fiber electrode;

[0051] The prepared conductive fiber membranes were neatly stacked in three layers and placed between orthogonally placed upper and lower flexible fiber electrodes, and finally packaged into a sensor using PI tape.

[0052] Example 3

[0053] Preparation of conductive fiber membrane: Polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 6:3:1 at 60°C, wherein the sum of the mass of PVDF, PAN, and Pluronic F127 accounted for 14wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 8 hours. The spinning solution was then electrospun at a voltage of 10.5kV, a receiving distance of 13cm, a drum speed of 100rpm, a solution supply rate of 0.6ml / h, a temperature of 32°C, and a humidity of 48RH%, to obtain a flexible PVDF / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0054] 0.4 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 6 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0055] Preparation of flexible fiber electrodes: The polymer TPU is completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 1:1 at 80°C, stirred for 12 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution is subjected to electrostatic spinning, with a spinning voltage of 14kV, a receiving distance of 20cm, a drum speed of 100rpm, a solution supply rate of 0.5ml / h, a temperature of 30°C, and a humidity of 50RH%, to obtain TPU nanofibers. The obtained nanofibers are cut into 20mm×20mm squares, and a silver paste with an area of ​​10mm×20mm and a thickness of 100μm is brushed in the middle of the square and then dried to obtain a flexible fiber electrode;

[0056] The prepared conductive fiber membranes were neatly stacked in three layers and placed between orthogonally placed upper and lower flexible fiber electrodes, and finally packaged into a sensor using PI tape.

[0057] Example 4

[0058] Preparation of conductive fiber membrane: Polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 6:3:1 at 60°C, wherein the sum of the mass of PVDF, PAN, and Pluronic F127 accounted for 16wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 8 hours. The spinning solution was then electrospun at a voltage of 10.5kV, a receiving distance of 13cm, a drum speed of 100rpm, a solution supply rate of 0.6ml / h, a temperature of 32°C, and a humidity of 48RH%, to obtain a flexible PVDF / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0059] 0.4 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 6 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0060] Preparation of flexible fiber electrodes: The polymer TPU is completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 1:1 at 80°C, stirred for 12 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution is subjected to electrostatic spinning, with a spinning voltage of 14kV, a receiving distance of 20cm, a drum speed of 100rpm, a solution supply rate of 0.5ml / h, a temperature of 30°C, and a humidity of 50RH%, to obtain TPU nanofibers. The obtained nanofibers are cut into 20mm×20mm squares, and a silver paste with an area of ​​10mm×20mm and a thickness of 100μm is brushed in the middle of the square and then dried to obtain a flexible fiber electrode;

[0061] The prepared conductive fiber membranes were neatly stacked in three layers and placed between orthogonally placed upper and lower flexible fiber electrodes, and finally packaged into a sensor using PI tape.

[0062] Example 5

[0063] Preparation of conductive fiber membrane: Polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 7:2:1 at 60°C, wherein the sum of the mass of PVDF, PAN, and Pluronic F127 accounted for 14wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 8 hours. The spinning solution was then electrospun at a voltage of 15kV, a receiving distance of 20cm, a drum speed of 100rpm, a solution supply rate of 1ml / h, a temperature of 32°C, and a humidity of 60RH%, to obtain a flexible PVDF / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0064] 0.4 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 6 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0065] Preparation of flexible fiber electrodes: The polymer TPU is completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 1:1 at 80°C, stirred for 10 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution is subjected to electrostatic spinning, with a spinning voltage of 20kV, a receiving distance of 30cm, a drum speed of 100rpm, a solution supply rate of 1ml / h, a temperature of 30°C, and a humidity of 50RH%, to obtain TPU nanofibers. The obtained nanofibers are cut into 20mm×20mm squares, and a silver paste with an area of ​​10mm×20mm and a thickness of 100μm is brushed in the middle of the square and then dried to obtain a flexible fiber electrode;

[0066] The prepared conductive fiber membrane is neatly stacked in one layer and placed between the upper and lower flexible fiber electrodes placed orthogonally, and finally clamped with PI tape to form a sensor.

[0067] Example 6

[0068] Preparation of conductive fiber membrane: Polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 8:1:1 at 60°C, wherein the sum of the mass of PVDF, PAN, and Pluronic F127 accounted for 14wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 8h. The spinning solution was then electrospun at a voltage of 15kV, a receiving distance of 20cm, a drum speed of 100rpm, a solution supply rate of 1ml / h, a temperature of 32°C, and a humidity of 60RH%, to obtain a flexible PVDF / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0069] 0.4 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 6 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0070] Preparation of flexible fiber electrodes: The polymer TPU is completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 1:1 at 80°C, stirred for 10 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution is subjected to electrostatic spinning, with a spinning voltage of 20kV, a receiving distance of 30cm, a drum speed of 100rpm, a solution supply rate of 1ml / h, a temperature of 30°C, and a humidity of 50RH%, to obtain TPU nanofibers. The obtained nanofibers are cut into 20mm×20mm squares, and a silver paste with an area of ​​10mm×20mm and a thickness of 100μm is brushed in the middle of the square and then dried to obtain a flexible fiber electrode;

[0071] The prepared conductive fiber membrane is neatly stacked in two layers and placed between orthogonally placed upper and lower flexible fiber electrodes, and finally clamped with PI tape to package it into a sensor.

[0072] Example 7

[0073] Preparation of conductive fiber membrane: Polycaprolactone (PCL), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 5:4:1 at 60°C, wherein the sum of the mass of PCL, PAN, and Pluronic F127 accounted for 12wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 8 hours. The spinning solution was then electrospun at a voltage of 20kV, a receiving distance of 25cm, a drum speed of 200rpm, a solution supply rate of 3ml / h, a temperature of 32°C, and a humidity of 75RH%, to obtain a flexible PCL / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0074] 1 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 3 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0075] Preparation of flexible fiber electrodes: The polymer SBS is completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 9:1 at 60-100°C, stirred for 12 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution is subjected to electrostatic spinning, with a spinning voltage of 35kV, a receiving distance of 35cm, a drum speed of 500rpm, a solution supply rate of 1.5ml / h, a temperature of 30°C, and a humidity of 70RH%, to obtain SBS nanofibers. The obtained nanofibers are cut into 20mm×20mm squares, and a silver paste with an area of ​​10mm×20mm and a thickness of 100μm is brushed in the middle of the square and then dried to obtain a flexible fiber electrode;

[0076] The prepared conductive fiber membranes are neatly stacked into four layers and placed between orthogonally placed upper and lower flexible fiber electrodes, and finally clamped with PDMS films to form a sensor.

[0077] Example 8

[0078] Preparation of conductive fiber membrane: Polyvinyl alcohol (PVA), polyacrylonitrile (PAN), and Pluronic F127 were completely dissolved in DMF at a mass ratio of 5:4:1 at 60°C, wherein the sum of the mass of PVA, PAN, and Pluronic F127 accounted for 10wt% of the mass of the spinning solution, and the spinning solution was obtained by stirring for 10 hours. Subsequently, the spinning solution was subjected to electrospinning, wherein the voltage was 9kV, the receiving distance was 7cm, the drum speed was 500rpm, the solution supply rate was 4ml / h, the temperature was 35°C, and the humidity was 30RH%, to obtain a flexible PVA / PAN / F127 mixed fiber membrane (i.e., a flexible nanofiber membrane).

[0079] 0.6 g of FeCl3·6H2O was added to an evaporating dish containing 200 ml of deionized water and stirred evenly. The prepared flexible nanofiber membrane was placed therein and allowed to stand at 0°C for 1 h. Subsequently, 0.4 g of pyrrole (Py) solution was added to react. After reacting for 3 h, the obtained conductive fiber membrane was taken out and washed with deionized water several times, and then placed in a forced air oven at 60°C for drying.

[0080] Preparation of flexible fiber electrode: The polymer SBS was completely dissolved in a mixed solvent of DMF / THF with a mass ratio of 9:1 at 80°C, stirred for 12 hours to obtain a spinning solution with a mass fraction of 22wt%, and the obtained spinning solution was subjected to electrostatic spinning, with a spinning voltage of 35kV, a receiving distance of 35cm, a drum speed of 500rpm, a solution supply rate of 1.5ml / h, a temperature of 30°C, and a humidity of 70RH%, to obtain SBS nanofibers. The obtained nanofibers were cut into 20mm×20mm squares, and silver paste with an area of ​​10mm×20mm and a thickness of 100μm was brushed in the middle of the square and then dried to obtain a flexible fiber electrode;

[0081] The prepared conductive fiber membranes were neatly stacked in five layers and placed between orthogonally placed upper and lower flexible fiber electrodes, and finally clamped with PDMS films to form a sensor.

[0082] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a flexible piezoresistive sensor based on conductive nanofibers, characterized in that: The steps include: S1. Preparation of conductive fiber membrane: polymer compound, polyacrylonitrile and Pluronic F127 are dissolved in an organic solvent to obtain a spinning solution, and then electrospinning is performed to obtain a flexible polymer mixed fiber membrane; the obtained flexible polymer mixed fiber membrane is placed in an oxidant solution, allowed to stand for a period of time, and then a conductive monomer solution is added to react for 4 to 20 hours, and a conductive fiber membrane is obtained after the reaction is completed; the mass ratio of the conductive monomer to the oxidant is 1:1 to 8:1; S2. Preparation of flexible fiber electrodes: a polymer compound is dissolved in an organic solvent to obtain a spinning solution and electrospinning is performed to obtain a flexible nanofiber substrate; then, a silver paste is brushed on the middle of the obtained flexible nanofiber substrate and dried to obtain a flexible fiber electrode; S3. The prepared flexible fiber electrode and the conductive fiber membrane are compounded together by stacking them layer by layer, and finally a sticky flexible film is used to package them into a sensor by sandwiching and pasting.

2. The method for preparing a flexible piezoresistive sensor based on conductive nanofibers according to claim 1, characterized in that: The polymer compound described in step S1 includes: at least one of polyvinyl alcohol, polystyrene, polyvinylidene fluoride, polyamide, polyacrylic acid and polycaprolactone; the mass ratio of the polymer compound, polyacrylonitrile and Pluronic F127 is 5:4:1 to 8:1:1, and the sum of the masses of the polymer compound, polyacrylonitrile and Pluronic F127 accounts for 8wt% to 20wt% of the mass of the spinning solution.

3. The method for preparing a flexible piezoresistive sensor based on conductive nanofibers according to claim 1, characterized in that: In step S1, when preparing the spinning solution, the polymer compound is first added, and then polyacrylonitrile is added, and an organic solvent is added to dissolve, and Pluronic F127 is added after the dissolution is uniform; the polymer compound, polyacrylonitrile and Pluronic F127 are all added to the organic solvent and stirred at 50-100° C. for 6-12 hours to obtain the spinning solution; The organic solvent described in step S1 is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, tetrahydrofuran, deionized water, and toluene; The electrospinning parameters described in step S1 are: spinning voltage 9-25 kV, receiving distance 7-40 cm, drum speed 100-5000 rpm, spinning solution supply rate 0.5 ml / h-4 ml / h, spinning time 4-10 h, spinning environment temperature 5-60 ° C, relative humidity 20-80 RH%.

4. The method for preparing a flexible piezoresistive sensor based on conductive nanofibers according to claim 1, characterized in that: In step S1, the oxidant is at least one of FeCl3·6H2O, ammonium persulfate, and sulfuric acid, and the conductive monomer is pyrrole or aniline; the concentration of the oxidant solution is 1g / L to 10g / L; the flexible polymer hybrid fiber membrane is placed in the oxidant solution and allowed to stand at -10°C to 10°C for 0.5h to 3h.

5. The method for preparing a flexible piezoresistive sensor based on conductive nanofibers according to claim 1, characterized in that: The polymer compounds described in step S2 are all elastic polymer compounds, specifically: one of polyurethane, polyethylene terephthalate, polystyrene-polybutadiene-polystyrene and polyamide; the organic solvent described in step S2 is at least one of N,N-dimethylformamide, tetrahydrofuran, acetone, formic acid, toluene and chloroform.

6. The method for preparing a flexible piezoresistive sensor based on conductive nanofibers according to claim 1, characterized in that: Preparation of the spinning solution in step S2: dissolving the polymer compound in an organic solvent and stirring at 60-100° C. for 6-18 hours to obtain the spinning solution; The electrospinning parameters in step S2 are: spinning voltage of 9 to 40 kV, receiving distance of 9 to 40 cm, drum speed of 100 to 5000 rpm, spinning solution supply rate of 0.5 ml / h to 1.5 ml / h, spinning time of 4 to 15 h, spinning environment temperature of 5 to 40 ° C, and relative humidity of 20 to 90 RH%.

7. The method for preparing a flexible piezoresistive sensor based on conductive nanofibers according to claim 1, characterized in that: In step S2, the flexible nanofiber substrate is cut into a suitable shape and then coated with silver paste. The silver paste with an area of ​​half that of the flexible nanofiber substrate and a thickness of 50 μm to 200 μm is evenly coated in the middle of the cut flexible nanofiber substrate. The size of the cut flexible nanofiber substrate in step S2 should be larger than that of the conductive fiber film. The flexible nanofiber substrate coated with silver paste is dried in an infrared lamp or oven for 10 to 40 minutes and then placed in the middle of a sticky flexible film.

8. The method for preparing a flexible piezoresistive sensor based on conductive nanofibers according to claim 1, characterized in that: When assembling the sensor in step S3, the conductive nanofiber film is stacked in 1 to 5 layers, aligned layer by layer, and placed between upper and lower flexible electrodes placed orthogonally; The adhesive flexible film in step S3 is selected from one of the following materials: polyimide tape, 3M tape, polyethylene film, polydimethylsiloxane film.

9. A flexible piezoresistive sensor made by the method according to any one of claims 1 to 8.

10. Application of the flexible piezoresistive sensor according to claim 9 in the fields of wearable devices, human-computer interaction, electronic skin and intelligent medical care.

Citation Information

Patent Citations

  • Method for preparing high-sensitivity flexible piezoresistive sensor based on fractured microstructure

    CN111982362A

  • Composite materials containing carbon nanoparticles

    CN101098916A

  • Electrostatic spinning method for preparing rare-earth metal doped nanometer lithium titanate

    CN102820460A